Requirements engineering: foundation for software quality 17th international working conference, REFSQ 2011, Essen, Germany, March 28-30, 2011 : proceedings - Berry, Daniel; Franch, Xavier (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 17th International Working Conference on Requirements Engineering: Foundation for Software Quality, REFSQ 2011, held in Essen, Germany, in March 2011. The 10 revised full papers and the 9 short papers presented were carefully reviewed and selected from 59 submissions. The papers are organized in seven topical sections on security and sustainability; process improvement and requirements in context; elicitation; models; services; embedded and real-time systems; and prioritization and traceability.